Association Between Youth Smoking, Electronic Cigarette Use, and COVID-19 - Gaiha, Shivani Mathur; Cheng, Jing; Halpern-Felsher, Bonnie (Journal of adolescent health, 2020)
This study aimed to assess whether youth cigarette and electronic cigarette (e-cigarette) use are associated with coronavirus disease 2019 (COVID-19) symptoms, testing, and diagnosis. An online national survey of adolescents and young adults (n = 4,351) aged 13–24 years was conducted in May 2020. Multivariable logistic regression assessed relationships among COVID-19–related symptoms, testing, and diagnosis and cigarettes only, e-cigarettes only and dual use, sociodemographic factors, obesity, and complying with shelter-in-place. COVID-19 diagnosis was five times more likely among ever-users of e-cigarettes only (95% confidence interval [CI]: 1.82–13.96), seven times more likely among ever-dual-users (95% CI: 1.98–24.55), and 6.8 times more likely among past 30-day dual-users (95% CI: 2.40–19.55). Testing was nine times more likely among past 30-day dual-users (95% CI: 5.43–15.47) and 2.6 times more likely among past 30-day e-cigarette only users (95% CI: 1.33–4.87). Symptoms were 4.7 times more likely among past 30-day dual-users (95% CI: 3.07–7.16). COVID-19 is associated with youth use of e-cigarettes only and dual use of e-cigarettes and cigarettes, suggesting the need for screening and education.